Upper extremity impairments, pain and disability in patients with diabetes mellitus. Issue 2 (June 2015) - Shah, K.M.; Clark, B.R.; McGill, J.B.; Mueller, M.J.
Abstract: Objectives: To determine the severity of, and relationships between, upper extremity impairments, pain and disability in patients with diabetes mellitus, and to compare upper extremity impairments in patients with diabetes with non-diabetic controls. Design: Case–control, cross-sectional design. Setting: University-based, outpatient diabetes centre and physical therapy research clinic. Participants: Two hundred and thirty-six patients with diabetes attending an outpatient diabetes clinic completed the Shoulder Pain and Disability Index (SPADI) questionnaire. A detailed shoulder and hand examination was conducted on a subgroup of 29 volunteers with type 2 diabetes, and 27 controls matched for age, sex and body mass index. Interventions: None. Main outcome measures: SPADI score, passive shoulder range of motion (ROM) and strength, grip strength, hand sensation, dexterity and limited joint mobility of the hand. Results: Sixty-three percent (149/236) of patients with diabetes reported shoulder pain and/or disability [median SPADI score 10.0 (interquartile range 0.0 to 39.6)]. Compared with the control group, the subgroup of patients with diabetes had substantial reductions in shoulder ROM, shoulder muscle strength, grip and key pinch strength ( P < 0.05). Patients with diabetes had a greater prevalence of decreased sensation (26/27 vs 14/27) and limited joint mobility of the hand (17/27 vs 4/27) compared with the control group. Total SPADI score was negatively correlated ( P < 0.05) with shoulder ROM ( r = −0.42 to −0.74) and strength measures ( r = −0.44 to −0.63) in patients with diabetes. Conclusions: Upper extremity impairments in this sample of patients with diabetes were common, severe and related to complaints of pain and disability. Additional research is needed to understand the unique reasons for upper extremity problems in patients with diabetes, and to identify preventative treatments.